Ensolisation-silylation reaction study of selected steroids. - Hehenberger, Anna; null, null; Kotas, Petr; Tříska, Jan (Institute of Analytical Chemistry AS CR, v.v.i., 2014)
For the purposes of trace analysis of 1,4-androstadiene-3,17-dione (ADD), 1,4-androstadiene-3-one-17β-ol (Boldenone) and 17-β-estradiol in water, waste water, soil and for the further phytosterols transformation studies the enolisation-silylation reaction was studied using MSTFA and BSTFA with different catalysts as derivatization reagents. The different reaction conditions and stability of the products was also studied using GC-MS technique.
Keywords: Ensolisation-silylation; reaction; study; selected; steroids.